Analytical study of the characteristic dispersion equations in elliptical step-index fiber with helical winding - Mishra, , Vivekanand; Kumar, , D (2005)
This paper reports the study of the electromagnetic optical wave propagation in elliptical structure with helical winding at different pitch angle. The elliptical coordinate system is used. The characteristic dispersion equation is obtained. By using of Mathieu and modified Mathieu functions. It is found that the dispersion curves are of the expected shapes. From these curves the number of sustained modes can be obtained for known values of the size parameter, the operating frequency, and the core cladding refractive index. If the circular waveguide is given a transverse compression at the extremities of the major axis, the distortion may be represented by elliptical waveguide. The purpose of the present communication is to obtain the characteristic dispersion equation for elliptical structure with helical windings. The application of the topics lies in their relationship to modem optical communication systems and polarization effect.